Personality Type D and Psychophysiological Stress Reactivity During Mental Stress in Young Healthy Individuals - Alexey N. Sumin; Natalia N. Zagorskaya; Anna V. Shcheglova; Anatoly A. Shipilov; Daniil Z. Kostylbaev; Elena A. Shikanova; Ingrid Y. Prokashko (Behavioral Sciences, 2025)
Persons with personality type D are characterized by an “unhealthy lifestyle”, which is manifested by low physical activity, less healthy eating behavior, and failure to comply with doctors’ recommendations. Persons with personality type D have an inadequate response of hemodynamic parameters to psychoemotional stress; the response of other parameters has not been sufficiently studied. The aim of this study was to investigate the association of personality type D with various psychophysiological parameters of the body during mental stress in healthy individuals. Material and Methods: The study involved 79 students of Kemerovo State Medical University aged 18 to 32 years (mean age 20.7 ± 2.4 years). Psychophysiological diagnostics was carried out using the BOSLAB complex; electromyogram, electrocardiogram, body temperature, respiration, galvanic skin response, and photoplethysmogram data were recorded. The stress testing protocol included cognitive tasks and recovery phases. Additionally, the presence of personality type D in students was assessed using the DS-14 questionnaire. The results of stress tests were compared in groups with the presence/absence of type D. Results: The frequency of detection of type D was high (54.4%). When examining the response of psychophysiological parameters, the most pronounced response to stress tests with mental load was noted for heart rate variability and respiratory system parameters. Individuals with type D personality showed more pronounced sympathetic activation in response to mental stress and a slower recovery at rest. Among the studied parameters, association with personality type D was noted for the following indicators during the mental arithmetic test: heart rate (p = 0.022), the Baevsky strain index (p = 0.004), respiratory rate (p = 0.020), and an indicator of regulatory process adequacy (p < 0.001). Conclusion: In the present study, we found differences in the reaction of psychophysiological parameters to mental stress in healthy individuals depending on the presence or absence of personality type D. These data can be useful for developing stress resistance programs and biofeedback training. The possibility of using the above psychophysiological parameters in biofeedback training programs for individuals with personality type D requires further research.